1986
DOI: 10.1093/nar/14.21.8605
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the cellulase genecelDencoding endoglucanase D ofClostridium thermocellum

Abstract: The nucleotide sequence of the celD gene, encoding the previously crystallized endoglucanase D of Clostridium thermocellum, is reported. The enzyme shares a conserved, reiterated domain with the COOH-terminal end of endoglucanases A and B from the same organism. The overexpression in Escherichia coli of celD subcloned in pUC8 appears to result from a translational fusion of the NH2-terminal end of the endoglucanase with the NH2-terminal end of beta-galactosidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 25 publications
3
51
0
Order By: Relevance
“…This assumption is supported by the finding that most functionally important residues identified in the six substrate-binding sites of CelD are conserved in CenC. In this context, it is interesting to note that both CenC (this study) and CelD (10,23,48) are highly active on chromophoric and fluorophoric glycosides derived from ␤-D-1,4-cellobiose and lactose. The absence of significant activity of CenB on these substrates supports the classification of CenC and CenB in different subfamilies (50).…”
Section: Discussionsupporting
confidence: 52%
“…This assumption is supported by the finding that most functionally important residues identified in the six substrate-binding sites of CelD are conserved in CenC. In this context, it is interesting to note that both CenC (this study) and CelD (10,23,48) are highly active on chromophoric and fluorophoric glycosides derived from ␤-D-1,4-cellobiose and lactose. The absence of significant activity of CenB on these substrates supports the classification of CenC and CenB in different subfamilies (50).…”
Section: Discussionsupporting
confidence: 52%
“…CelF, the CelS equivalent in C. cellulolyticum, also displays significant activity in reducing the viscosity of a CMC solution (271). Some of the cloned endoglucanase genes are celA (26), celB (105), celC (298), celD (143,326), celE (113), celF (245), celG (188), celH (361), celI (101,123,373), celJ (encoding component S2 of the complex) (1,8), celM (162), celN (373), celQ (9), celT (172), and celX (113).…”
Section: Genes and Enzymesmentioning
confidence: 99%
“…A large number of genes have been identified that code for various endoglucanases (Beguin et al, 1985 ;Grepinet & Beguin, 1986;Joliff et al, 1986; McGavin & Forsberg, Substrate spec8city and enzyme assays. The E. coli periplasmic fraction was used for substrate specificity assays for the cloned enzyme.…”
Section: Introductionmentioning
confidence: 99%